À quel prix vêt-on la terre ou le vent ? Regards mulongo sur le vêtement dans La Saison de l’ombre de Léonora Miano - Pierre-Yves Dufeu (Itinéraires)
How are clothing and garment perceived in La Saison de l’ombre (Léonora Miano, 2013)? Through these superficial referents, the narrative makes the reader perceive the intercultural depth of exchanges woven in the early days of the slave trade, the “season of the shadow” for African societies. In this fiction the various anthropological functions of the garment, which are in turn foregrounded, accompany and signify the historical process of reification and assignment to the fungible of man himself. Told empathically, the story makes the reader identify with the Mulongo community, who, very early in the novel, fall victim to a fire and inexplicable disappearances. For this community, clothing, taken from the forest, protects as the forest does. Any cloth, skin or beaten bark is used to clothe and to protect. Clothing is a women’s matter and is strongly associated with their voices, their work and presented as a sign of their strength by the author. But the story also recounts the astonishment of a Mulongo character when faced with his Bwele neighbors’ art of weaving, and with the strange and threatening customs associated with their fabrics, woven by men and sometimes used to cover the earth rather than bodies. Further still, on the coast, the unimaginable end of the world for forest Mulongos, even more dangerous foreign fabrics are able to imprison the wind itself as well as women’s desire for elegance and men’s thirst for power. These are the mental and symbolic, cultural and historical boundaries that the reader will have crossed throughout the story by looking at fabrics through Mulongo eyes.